1986
DOI: 10.2307/2061617
|View full text |Cite
|
Sign up to set email alerts
|

Biosocial foundations for adolescent female sexuality

Abstract: Despite the widespread assumption that hormones stimulate motivation for sexual behavior in adolescence, no published empirical studies have demonstrated this link. In a cross-sectional study of 78 females in the eighth, ninth, and tenth grades in public schools, we show that hormones have effects on sexual motivation and behavior. Comparison with previous results from a parallel sample of males indicates that for both sexes these effects are primarily androgenic in origin and for the most part exert their eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0
3

Year Published

1996
1996
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(72 citation statements)
references
References 19 publications
1
68
0
3
Order By: Relevance
“…Second, a discriminant function analysis was conducted to identify the constellation of variables that best discriminated among the different timing groups. All analyses were conducted separately for boys and girls, because there is evidence that biological and social factors differentially predict sexual intercourse for the two genders (Udry et al, 1985(Udry et al, , 1986.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, a discriminant function analysis was conducted to identify the constellation of variables that best discriminated among the different timing groups. All analyses were conducted separately for boys and girls, because there is evidence that biological and social factors differentially predict sexual intercourse for the two genders (Udry et al, 1985(Udry et al, , 1986.…”
Section: Discussionmentioning
confidence: 99%
“…One perspective emphasizes biological factors, with adolescent sexual activity being tied to the biological changes of puberty . In line with this perspective, pubertal hormones (especially androgens) appear to be associated with sexual motivation and intercourse experience in males (Udry et al, 1985) and with sexual motivation and precoital sexual experience in females (Udry et al, 1986). Moreover, the timing of puberty appears to be associated with age at sexual initiation: early maturing girls tend to experience intercourse at younger ages than do later maturing girls (Magnusson, 1988 AND ADOLESCENCE 25 (1996) TIMING OF FIRST SEXUAL INTERCOURSE 93 early age and thus experience opportunities (and possibly pressure) to engage in intercourse before later maturers do.…”
Section: Explanations Of Adolescent Intercoursementioning
confidence: 91%
“…Testosterone administration increases sexual interest and behavior in women (Sherwin, Gelfand, & Brender, 1985) and in men with low testosterone levels (Kwan et al, 1983). Similarly, cross-sectional studies by Udry and colleagues demonstrated an association between androgen levels and both sexual motivation and behavior in early adolescence Udry, Talbert, & Morris, 1986). However, lon gitudinal studies have not supported this linkage: increases in testosterone over early adolescence failed to predict changes in sexual behavior for either gen-der (Udry & Campbell, 1994).…”
Section: Pubertymentioning
confidence: 99%
“…Measures that use this approach have been used in other research on physical development and are correlated with more detailed measures based on direct observations. 11,12 Parents also were asked whether they thought their adolescent was currently involved in a romantic relationship with a member of the opposite sex.…”
Section: Physical Development and Relationshipmentioning
confidence: 99%